Trainees’ views of physician workforce policy in Quebec and their impact on career intentions - Hallet, Julie (Can Med Educ J, 2014)
BACKGROUND: The physician workforce in Quebec is regulated by a government-controlled plan. Many specialty trainees expressed concerns about securing a position. Our objective was to analyze physicians’ employment issues in Quebec and their impact on residents’ training in specialty programs. METHODS: We distributed a web-based self-administrated survey to all Quebec residents training in specialty programs to capture data about residents’ ability to find employment, career plans and perceptions regarding the workforce policy. Three groups were considered: graduates, non-graduating senior residents, and junior residents. RESULTS: The overall response rate was 41.5% (985/2372). 47.3% of graduates did not have a position two months before finishing their training. Among residents without a position, 27.1% of graduates intend to leave Quebec, and 19.6% to complete a fellowship to postpone their start in practice. Overall, 77.9% of respondents believed there are not enough job opportunities for the number of trainees. CONCLUSION: Quebec specialty residents experience significant difficulties obtaining a position in the province and perceive that there are not enough job opportunities, which impacts their career plans and could drive them to complete a fellowship or plan to practice outside the province. Trainees’ experience in finding employment needs to be considered in planning the physician workforce.